Assessment of CSR Performances in Some Selected Commercial Banks in Bangladesh - Azad, Md. Abul Kalam; Raihan, Mohammad Zahir; Bhuiyan, Mohammad Zahid Hossain (Global Disclosure of Economics and Business, 2013)
The study is on 10 locally private commercial banks operating in Bangladesh. In this study, secondary data have been extensively used. Some primary data have also been used in the study. These were collected from a total number of 10 Executives in-charge of Corporate Social Responsibility Department using structured closed end questionnaire. While collecting primary data, direct interview method was mainly used. The main objective of the study is to critically analyse the CRS performances in the selected banks which covered the Heads of CSR activities, the determinants of CSR activities, Investment in CSR activities and Impact of CSR investment. The period of empirical study covered 4 financial years ranging from 2009 to 2012.  The main findings of the study are; (i) some 90% of the respondents have emphasized on the significance of CSR activities in the selected banks, (ii) some 60% of the respondents have emphasized on the significant impact of CSR investment on the Market price of the Share (MPS), (iii) the major factors affecting CSR activities have been Sustainable development, Business tool, Leadership and ethics, (iv) empirical analysis of the study reveals that the CSR investments as percentage of total investment of the respective banks have been very negligible ranging from 0.01% to 2.87% only during the study period. It is found that out of the seven heads of CSR expenditures Health sector have occupied the highest position in majority banks followed by Education sector. Therefore, it can be concluded that the selected banks should increase their investment in CSR activities in order to create more confidence among the existing clients as well as prospective customer in one hand and increase MPS of the banks on the other.JEL Classification Code: G21; G28